The relationship between gender, age, depression and academic achievement. - Yousefi, Fayegh; Mansor, Mariani; Juhari, Rumaya; Redzuan, Ma'rof; Abu Talib, Mansor (2010)
is said to have a relationship with academic achievement. Thus, the purpose of the study was to investigate the relationship between age, depression and academic achievement among adolescents. Approach: The study was carried out among 400 students (200 boys and 200 girls) in the age range 15-19 years. The instrument used for data collection was the Beck Depression Inventory (21 item BDI). The analysis of data used correlation coefficient and t-test. Results: The results showed that 27.5% of the boys and 31.5% of the girls were depressed and that depression and academic achievement were significantly correlated, r = -0.22, p≤0.000. Also, based on results of the present study, age and academic achievement were significantly correlated (r = 0.23, p≤0.000). In addition there was significant difference of academic achievement between male and female, (t (1) = -5.47, p = 0.000). Conclusion/Recommendations: It is recommended that along with academic achievement, mental health be developed in school settings using support strategies such as educational guidance and counseling, teaching life skill programs and psychotherapy.